SETDB1 knockdown boosts recombinant protein in CHO cells via epigenetic transcriptional silencing - Jiang-Tao Lu; Miao Zhang; Yan-Ping Gao; Lu-Lu Yang; Zhao-Ming Cui; Ming-Ming Han; Xi Zhang; Hong-Yan Xu; Xiao-Yin Wang; Le-Le Qiu; Zi-Chun Hua; Tian-Yun Wang; et al. (AMB Express)
Abstract Chinese hamster ovary (CHO) cells serve as the predominant mammalian expression system for recombinant protein production. However, clonal heterogeneity and instability in recombinant protein expression remain significant challenges. SET domain bifurcated histone lysine methyltransferase 1 (SETDB1) catalyzes histone 3 lysine 9 trimethylation (H3K9me3), a critical epigenetic modification regulating gene expression. Despite its functional importance, the dynamics of SETDB1 expression and its regulatory impacts in CHO cells remain poorly characterised. Through transcriptomic analysis of high- and low monoclonal antibody (mAb)-producing CHO clones, we identified SETDB1 as a key modulator of mAb expression. Notably, SETDB1 expression exhibited an inverse correlation with recombinant protein levels in transfected CHO cells. SETDB1-knockdown (SETDB1-KD) CHO cells demonstrated significantly enhanced recombinant antibody-specific productivity. The use of small-molecule SETDB1 inhibitors resulted in a comparable enhancement of transgene expression to that observed with SETDB1 silencing. During extended cultivation, recombinant protein production progressively diminished concurrent with declining SETDB1-KD efficacy. This temporal correlation demonstrates that SETDB1-mediated epigenetic regulation is essential for maintaining both recombinant protein titers and chromosomal stability in industrial biomanufacturing processes. Transcriptome dynamics analysis revealed that SETDB1 silencing induces transcriptional pattern remodeling in transfected cells. These findings elucidate SETDB1's regulatory role in CHO cells and provide actionable insights for the optimisation of recombinant protein production through cell engineering strategies.